Stress and coping in relation to gender and domicile among college students in Kashmir - Dar, Imtiyaz Ahmad; Iqbal, Naved (National Science Foundation: Colombo, 2019)
Due to the long standing conflict, people in Kashmir, particularly college students, are subjected to constant stress. This has deleterious effects on their well-being and education. Unlike in safe situations, students living among conflict situations may have different experiences of stress and ways of dealing with it. As per transactional theory of stress and coping, the perception and reaction to the stressors may vary considerably among people. This variance may be attributed to some factors such as gender and domicile. Research regarding the role of gender and domicile on stress and coping is inconsistent and scarce. Therefore, the purpose of the current study was to examine the impact of gender and domicile on stress and coping among a sample of 80 college students in Kashmir. A 2*2 factorial design was employed for analysis. Results suggest that male participants display higher stress levels than female participants, if they belong to a rural domicile. Further, it suggests that all rural and female participants, in general, employ distancing coping strategy more frequently than their counterparts. In addition, female participants employ accepting responsibility as a coping strategy more frequently than male participants, if they belong to a rural domicile. Male participants, on the other hand, were found to employ positive reappraisal as a coping strategy more frequently than females; however, this was the case when their domicile was urban. Lastly, urban male participants were found to employ accepting responsibility and positive reappraisal as coping strategies more rigorously than rural males.
Keywords: Conflict; Stress; Coping; College students; Gender; Domicile